Factors promoting daily usage of alcoholic substances in Ubungo District - Joshua Juma Mugane; Michael B. Welwel; Alvin A. Kessy (Indonesian Journal of Social Sciences, 2023)
Topics concerning the usage of alcoholic substances have always caught the attention of different health science and social science professionals because of the tenacious growth in alcohol consumption and its effects. Due to such a fact, this study was conducted in Ubungo District in order to determine the factors that promote the daily usage of alcoholic substances. A cross-sectional research design and purposive sampling were employed to manifest data collection within a sample size of 240. The obtained data were gathered through semi-structured interviews and presented in tables, showing frequencies and percentages. The results show that alcoholic substances are daily consumed due to the availability of alcoholic centers, low/affordable price of alcoholic substances, the nature of works of people, bundles promotion and offers from friends/relatives, family history of the users, less purchasing restrictions, individual’s perception on alcoholic beverages, advertisement of the substances on media, and alcohol dependency and addiction. Finally, rescuing the alcohol addicts, the concerned authorities should set and enforce rules and restrictions concerning the sales and consumption of the substances; and provide psycho-educational programs and seminars on abandoning alcohol abuse, dependency, and addiction, so as to minimize financial bankruptcy and other social or family conflicts brought about by daily consumption/usage of alcoholic substances.